2022
DOI: 10.3390/land11070962
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Attributes for Sustainable Wetland Management in Mpologoma Catchment, Uganda: A Discrete Choice Experiment

Abstract: Sustainable wetland management is a focus of many countries worldwide. These mainly use protection as a key policy directive for conservation. However, avoidance directives tend to disenfranchise local populations. Thus, such management is often resisted and rarely effective. Tailoring management strategies to user preferences allows conservation to support community livelihoods for sustainable development. This study employed a discrete choice experiment to determine the wetland management attributes preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 74 publications
0
2
1
Order By: Relevance
“…Speci cally, a movement higher, across education categories, decreased the likelihood of using soil and water conservation practices and conservative livestock keeping practices by 11 and 10 percent respectively with regard to non-use of wetland management practices. Contrary to this study, Bunyangha et al (2022) found a positive effect of education to wetland management. Shah and Atisa (2021) found education had no effect on wetland biodiversity conservation.…”
Section: Determinants Of Use Of Wetland Management Practices Among Us...contrasting
confidence: 99%
See 2 more Smart Citations
“…Speci cally, a movement higher, across education categories, decreased the likelihood of using soil and water conservation practices and conservative livestock keeping practices by 11 and 10 percent respectively with regard to non-use of wetland management practices. Contrary to this study, Bunyangha et al (2022) found a positive effect of education to wetland management. Shah and Atisa (2021) found education had no effect on wetland biodiversity conservation.…”
Section: Determinants Of Use Of Wetland Management Practices Among Us...contrasting
confidence: 99%
“…Description of variables Those with higher education were expected to use more practices to manage the wetland. AlthoughShah and Atisa (2021) found that education had insigni cant effect on changes in biodiversity,Bunyangha et al (2022) found education to have a positive effect on wetland management. Use of fertilizer was a dummy, one for use of fertilizer and zero otherwise.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The human population density is moderate by national standards at 260 persons per km². The annual rainfall range is 900-1500 mm, and the vegetation is mainly composed of savanna species (Bunyangha et al, 2022). To understand the mediating role of management functions in influencing Limoto wetland restoration, both quantitative and qualitative data were collected using household interviews, key informant interviews, and field observations.…”
Section: Location Of the Study Areamentioning
confidence: 99%
“…According to An & Verhoeven, (2019), ecological restoration is one of the fastest-growing fields in applied ecology providing new ideas and opportunities for biological conservation and natural resource management. However, despite countless attempts in the past (Roe et al, 2015), several restoration projects have fallen short of being considered successful (Bunyangha et al, 2022;Obubu et al, 2022). Kakuba & Kanyamurwa, (2021) note that these shortfalls could be as a result of one or a combination of the following mainly: unrealistic goals; inadequate restoration plans based on an ad-hoc approach; lack of explicit and quantified evaluation criteria for restoration success; lack of ecological understanding; social, economic, and political constraints.…”
Section: Introductionmentioning
confidence: 99%